The Effect of Service Quality, Competence, and Innovation on the Marketing Performance of Course and Training Institutions in Semarang Regency, Central Java - Heru Yulianto; Dimas Adi Wicaksono; Amsar Amsar (Khazanah Sosial, 2025)
This study aims to empirically examine the effect of service quality, competence, and innovation on the marketing performance of Course and Training Institutions (Lembaga Kursus dan Pelatihan, LKP) in Semarang Regency, Central Java. The background of this research is based on the importance of the role of LKPs in improving human resource quality through professional, competent, and innovative non-formal education, which allows them to compete in the global era. This research uses a quantitative approach with a descriptive and causal design. Data was obtained through a survey using questionnaires and structured interviews with 150 respondents, who were managers of LKPs (Directors, Secretaries, Treasurers, Public Relations, and Marketing Administration). Data analysis was conducted using multiple linear regression tests with the coefficient of determination (R²) and partial (t-test) and simultaneous (F-test) significance tests. The results of the study show that service quality, competence, and innovation have a positive and significant effect on the marketing performance of LKPs, both simultaneously and partially. Innovation is the most dominant factor, followed by competence and service quality. These findings emphasize that LKPs capable of providing quality services, having competent management, and continuously innovating will be more successful in building their image, increasing competitiveness, and expanding marketing networks. The implications of this research emphasize the importance of policies that expand access to competence certification, encourage the digitalization of learning and marketing, and strengthen partnerships between LKPs and the business and industrial world (DUDI). Thus, the results of this research can contribute to improving the quality of non-formal education and provide practical guidance in managing LKPs in Indonesia. The originality of this research lies in its empirical study focus on LKPs in the local context of Semarang Regency, which has not been extensively researched. In addition to providing quantitative evidence on the determinants of marketing performance in non-formal educational institutions, this study also enriches the literature by emphasizing the role of innovation as the most influential variable in strengthening the competitiveness of non-formal institutions in the era of digital transformation.